Oxygen and carbon isotopes from foraminifers and benthic foraminiferal abundance at DSDP Holes 71-511 and 71-512 - Jay Phillip Muza; Douglas F Williams; Sherwood W Wise (PANGAEA, 1983)
An Eocene-Oligocene oxygen and carbon isotope history based on planktonic and benthic foraminifers from Deep Sea Drilling Project Leg 71 cores has been constructed for the Maurice Ewing Bank of the eastern Falkland Plateau, Southwest Atlantic Ocean. Specifically, the cores cover portions of the middle Eocene, upper Eocene, and lower Oligocene. Surface water isotopic temperatures postulated for the middle Eocene at Site 512 fluctuated within about four degrees but generally averaged about 9°C. Bottom isotopic temperatures at Site 512 (water depth, 1846 m) were generally a degree lower than surface water temperatures. Surface water isotopic temperatures at Site 511 initially averaged about 11°C during the late Eocene, but dropped to an average of 7°C in the early Oligocene. Bottom isotopic temperatures at Site 511 (water depth, 2589 m) generally record temperatures between 12.5°C and 8°C, similar to the range in the surface water isotopic temperatures. During the early Oligocene, bottom isotopic temperatures dropped sharply and averaged about 2°C (very close to present-day values). Surface water temperature values also decreased to an average of about 7°C, therefore leading to a significant divergence between surface and bottom water isotopic temperatures during the early Oligocene. Comparisons among Southern Ocean DSDP Sites 511, 512, and 277, and between these and other DSDP sites from central and northern latitudes (Sites 44, 167, 171, 292, 357, 398, 119, and 401) show that much of the Eocene was characterized by relatively warm temperatures until sometime in either the middle Eocene, late Eocene, or early Oligocene. At each site, conspicuous 18O enrichments occur in both the benthic and planktonic foraminifers over a relatively short period of time. Although a general trend toward a climatic deterioration is evident, the density of data points among the various studies is still too sparse to determine either synchrony or time-transgression between the major isotopic events. A close correlation could be made between the Site 511 oxygen isotope temperature curve and paleoclimatic trends derived independently from radiolarian studies. The sharp temperature drop and the divergence between bottom and surface water temperatures during the early Oligocene apparently reflect a major expansion of the antarctic water mass. The migration of the boundary between the subantarctic and antarctic water masses over the site at this time would account in part for the sharp temperature changes. Sharp changes of this nature would not necessarily be noted in other geographic areas, particularly those to the north which have different oceanographic regimes.
Supplement to: Muza, JP et al. (1983): Paleogene oxygen record for Deep Sea Drilling Project Sites 511 and 512, subantarctic South Atlantic Ocean: Paleotemperatures, paleoceanographic changes, and the Eocene/Oligocene boundary event. In: Ludwig, WJ; Krasheninnikov, VA; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 71, 409-422, https://doi.org/10.2973/dsdp.proc.71.117.1983